Associations of nutritional awareness, body mass index, mental health, and fitness components among undergraduate university students - AlKilani, Laila Fathi Zaid; Awad, Salwa Saad; ALTamimi, Jozaa Zaidan; Alharbi, Fatimah Sayer (Frontiers in Nutrition, 2025)
IntroductionThe study generally aimed to examine nutritional awareness, body mass index, mental health, dietary awareness, and components of physical fitness among university students by investigating the health behaviors, physical activity, diet, sleep, internet use, and mental health of 153 undergraduate university students.MethodsThis study employed a cross-sectional quantitative survey method to evaluate the risky and health-related behaviors, psychological health, and health-related behaviors of female university students.ResultsAmong them, 66% did not engage in high-intensity physical activities, and 54.9% did not participate in moderate-intensity workouts. Of the participants, 52.9% ate two meals a day, and 43.1% only sometimes ate breakfast. According to the survey, 56% recognized smoking as a contributing factor to health problems, and 60% said stress had a major effect on health problems. Moreover, the results reveal a statistically significant relationship between weight category and depression symptoms (r = −0.06, p = 0.53) and between physical activity and depression symptoms (r = −0.11, p = 0.23).DiscussionThe findings call which calls for encouraging the increase of such studies in the future and conducting them on a larger sample and encouraging the adoption of university programs aimed at raising awareness of the importance of physical activity, healthy nutrition, and mental health.